CONTAMINATION ESCHERICHIA COLI IN BROILER CHICKEN MEAT SOLD AT BADUNG MARKET, DENPASAR, BALI DURING THE TRANSITION SEASON - Riki Jainudin; Hapsari Mahatmi; Romy Muhammad Dary Mufa; Gede Putra Sanjaya (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Escherichia coli is reported as an intensive bacterial contaminant of chicken meat, including broiler meat. Factors that support the occurrence of contamination are the environment, equipment and sellers. This study aims to determine the presence of Escherichia coli bacteria in broiler meat sold in Badung market, Denpasar, Bali during the transitional season. The samples used were fresh broiler meat totaling 15 samples by taking randomly from 15 broiler meat traders. Samples will be taken to the laboratory for isolation and identification of Escherichia coli. The isolation stage uses selective media, namely Eosin Methylen Blue Agar (EMBA), identifying with the gram staining method, and biochemical tests consisting of Triple Sugar Iron Agar (TSIA), Citrate, Indol and Methyl Red tests. The results of the study found 3 (20%) of the 15 samples identified were contaminated by Escherichia coli bacteria. From the results of this study there is still contamination of Escherichia coli bacteria and needs to get more attention from the government in order to get education about the procedures for selling broiler meat according to standards and implement applicable regulations more strictly, because it affects public health.